Characterization of negative electrolyte– alizarin red s and positive electrode felt for organic redox flow battery application - Khor, Ai Chia (2021)
Organic redox flow battery (ORFB) is considered as one of the sustaining technologies for large scale energy storage. Among the organic redox flow battery technology, quinone redox couple is one of the attractive solutions as organic electrolyte because of the lowcost, multiple electron and eco-friendly solution. Organic quinone redox material such as abundantly available alizarin red s with two electron reduction reaction and electronegative potential (c.a. 0.082 V vs. standard hydrogen electrode) is suitable to be applied as negative electrolyte for ORFB application. There is a lack of scientific investigation of alizarin red S (ARS) at various concentration which the previous studies on ARS concentration are limited to 50m mol dm-3 and 1 mol dm-3 supporting acid concentration. This work aims to investigate the electrochemical characteristics of ARS with respect to different composition of redox active and sulphuric acid concentration. Consequently, the first part of this work introduces experimental work for alizarin red S (ARS) organic dye with three proposed concentrations of ARS (0.05, 0.10 and 0.15 mol dm-3) and two concentration of supporting electrolyte – sulphuric acid which are 1 mol dm-3 and 2 mol dm-3. Electrochemical study such as cyclic voltammetry has been conducted under several operating conditions (i.e., ARS concentration and acid concentration). In summary, the result indicates that ARS highly reversible at 0.05 mol dm-3 and 1 mol dm-3 sulphuric acid with calculated diffusion coefficient of 6.424 x 10-4 cm2 s-1. Another key component that determines the performance of RFB is electrode. In RFB application PAN type carbon felts are widely used as the electrodes, however, pristine carbon felts suffer from low surface properties on electrode due to the hydrophobic characteristics and poor catalytic activity towards quinone species. There is a lack of scientific investigation on combined methods on electrode treatment. Most importantly, the study between the change in electrode physiochemical and electrochemical properties in quinone based electrolyte need to be investigated. A novel of two stage treatment on electrode surface by using three different oxidation methods – acid, alkaline and hydrogen peroxide combined with thermal are carried out on carbon felts. The preparation method is inexpensive, and the study has been extended to the comparison between alkaline and hydrogen peroxide treated carbon felt investigation in selected positive electrolyte, benzoquinone. The results from characterization to identify the surface composition, surface morphology and wetting characteristics that relate to the electrochemical performance such as reversibility and electron diffusion are presented in this work. This study has successfully demonstrated the application of two stage surface treated felt with respect to physiochemical and electrochemical with aims to enhance the positive half-cell of ORFB. The comparison work concludes that CFH2SO4 presented the best reversibility compared to pristine felt, CFH2O2 and CFNaOH with the difference between the anodic and cathodic peak (ΔE) near to 59mV and Ipa/Ipc ratio <1 demonstrated good reversibility. The work reports no significant change on the surface of hydrogen peroxide with thermal. In addition, oxygen functional group such as C-O, COH, C=O and C-C=O are successfully introduced onto the surface of treated carbon felt as the result of improved wettability properties of treated carbon felt supported by the finding in contact angle measurement, and it can enhance the kinetics reaction in BQ solution. From previous findings, it has found out that quinone based redox material demonstrates the best redox activity under acidic environment. As a result, this study is extended to investigate the effect of supporting acid (methanesulfonic acid and sulphuric acid). The findings reveal that CFH2SO4 shows good reversibility in sulphuric acid compared to methanesulfonic acid.